Richness and diversity of alien ethnomedicinal plant taxa used and sold for traditional medicine in South Africa - Wojtasik, Ewa Mariola (My University, 2014)
In South Africa, indigenous plant species are used and traded for traditional medicine (muthi) and so are alien plant species. A literature review of 40 previous studies and survey work at various outlets, including muthi markets and muthi shops in Johannesburg, Durban and Pretoria, found that 320 alien plant species are used and/or sold for traditional medicine in South Africa. Fifty three of the 320 species were found to have weed and/or invader status. Surveys at Faraday and Warwick muthi markets in Johannesburg and Durban respectively as well as muthi shops in Johannesburg, Durban and Pretoria were conducted from October 2010 to February 2011. The following aspects regarding the plant material traded were recorded: the differences in the number of volumes traded; the differences in the number of alien species sold in the markets and shops (and also in Indian and Black-owned shops); the source and origins of these and the viability of propagules sold in the muthi trade. The surveys found that 49 alien plant species were sold and approximately 87 x 50kg-size bags of alien plant material was present in the markets and shops during the time of the survey. Muthi shops sold more than double the number of alien plant species than were sold in the markets and the same result was found for Indian versus Black-owned shops. Alien species were either harvested in South Africa, predominantly in KwaZulu-Natal (KZN), or imported from India. Indian-owned muthi shops sold more species imported from India than alien species that were naturalised and harvested in South Africa. In contrast, the majority of alien species sold at markets and Black-owned shops were harvested in KZN. Viability tests found that 24% of alien plant species sold in this study had greater than 50% viability. Six invasive species are traded in low volumes with viable propagules sold for five of these, highlighting a possibility of spreading through the traditional medicine trade. The study concluded that the total trade in alien plant species is trivial in comparison to the trade of indigenous plant species.
Keywords: Traditional medicine - South Africa.; Ethnology - South Africa.